(untitled) (Cadernos de Psicologia Social do Trabalho, 2003)
This article deals with a number of methodological and theoretical questions in connection with intervention research in the field of psychosocial factors at work. These interventions can take place at different levels from the individual to the macro level of society. Also, the interventions can be primary (reducing stressors at work), secondary (reducing stress, burnout, etc.) and tertiary (reducing the long term consequences of work-related stress). Most research in this field has so far has been at the individual level and of the secondary/tertiary type. This is explained by the fact that both managers and psychologists have preferred this type of intervention in the past. The research activity in the field has been expanding and improving during the last years, but a number of challenges still remain. Some of the important problems are: 1) Lack of a proper analysis; 2) Poor intervention designs; 3) Problems with selection and confounding factors; 4) Poor distinction between aetiological and feasibility studies. It is emphasized that practical issues relating to structural, economic, legal and psychological factors at the workplace often will put restrictions on the researcher, which means that less than optimal designs and follow-up periods has to be accepted. In the conclusion the authors recommend the use of multiple case studies in future intervention research.